Cereal straw as a resource for sustainable biomaterials and biofuels : chemistry, extractives, lignins, hemicelluloses and cellulose - Sun, Runcang (Elsevier, 2010)
The first book to examine straw chemistry in its entirety, Cereal straws describes the recent development of techniques for fractionation of and conversion to environmental friendly materials. Balanced coverage of theory and applications includes: the analysis of straw structure and its components; extractives, from isolation to structural characterization; isolation, modification, and purification of hemicelluloses; the occurrence, structure, and chemical modification of cellulose; straw lignins, including their occurrence, structure and constitution, isolation and heterogeneity, and physico-chemical properties; and utilization of straw and straw components after chemical modification. Provides the basics of straw composition and the structure of its cell walls. Details the procedures required to fractionate straw components to produce chemical derivatives from straw cellulose, hemicelluloses, and lignins. Elucidates new techniques for the production of biodegradable materials for the energy sector, chemical industry, and pulp and paper business.